PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI METODE STRUKTURAL ANALITIK DAN SINTETIK (SAS) KELAS I SD INPRES TIMBUSENG KABUPATEN GOWA - Mutmainna; Nurhadifah Amaliyah; Bellona Mardhatillah Sabillah; Muh.Khaedar (STKIP Subang, 2024)
This study aims to determine the use of the Analytical and Synthetic Structural Method (SAS) can improve the early reading skills of grade I students of SD Inpres Timbuseng, Gowa Regency. This study uses a qualitative approach with a classroom action research (CAR) design. In 2 cycles, each consisting of three meetings. Data were collected through teacher and student observations, Completeness, and interviews with teachers. The results of the study showed that the use of the Structural Analytical and Synthetic (SAS) method in early reading learning succeeded in significantly improving students' reading ability. In cycle I, the application of the SAS method showed an increase in students' early reading ability, including improvements in recognizing letters, reading words, and understanding simple sentences, although completeness was still relatively low (20% at the first meeting, 40% at the second meeting, and 45% at the second and third meetings). In cycle II, the application of the SAS method showed significant progress, with completeness reaching 50% at the first meeting, 70% at the second meeting, and 95% at the third meeting, as well as an increase in students' ability to read more complex texts.